A novel double fusion of EML4-ALK and PLEKHA7-ALK contribute to rapid progression of lung adenocarcinoma: a case report and literature review - Zhongzhao Wang; Yang Luo; Heng Gong; Yang Chen; Hao Tang (Discover Oncology)
Abstract A 40-year-old male with EML4-ALK (E6:A20) fusion variant 3 and previously unreported PLEKHA7-ALK (P3:A20) fusion in lung adenocarcinoma exhibited resistance to alectinib and chemotherapy. Subsequent next-generation sequencing (NGS) from the plasma specimen revealed the co-existing mutation in the KEAP1 gene, which may represent an intrinsic resistance to ALK-TKI. Furthermore, the presence of double fusion PLEKHA7-ALK (P3:A20) may also have played a critical role in the resistance to alectinib. KEAP1 mutation (p.E244K) was also founded in this patient which may lead to resistance to standard chemotherapy. The patient was then treated with brigatinib, which effectively halted the rapid progression. Unfortunately, the patient deceased to uncontrollable, rapidly progressing pleural effusion and pulmonary embolism, resulting in an overall survival of 9 months. This represents the rare case of NSCLC with a double fusion of EML4-ALK and PLEKHA7-ALK, exhibiting resistance to alectinib and chemotherapy. Our case suggests that the double fusion of EML4-ALK and PLEKHA7-ALK and co-existing KEAP1 mutation may serve as an adverse prognostic factor. Additionally, brigatinib may offer a potential treatment option for lung adenocarcinoma patients with PLEKHA7-ALK (P3:A20) fusion.